The Oxford Handbook of the Sociology of Disability 2021
DOI: 10.1093/oxfordhb/9780190093167.013.16
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure, Discrimination, and Identity among Working Professionals with Bipolar Disorder or Major Depression

Abstract: This chapter presents the results of an analysis of in-depth interviews with a snowball sample of 45 people who identified as working professionals diagnosed with bipolar disorder or major depression. It explores three dimensions of their experience: disclosure versus concealment of their diagnosis on the job, exposure to discrimination in the workplace based on their mental illness diagnosis, and identity strategies they used to manage the status inconsistency between being a professional and having a mental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…The current study addresses important gaps in research on workplace disclosure of SMI by sampling both currently and formerly employed workers, from previously unstudied geographic contexts and a wide range of employment settings, and collecting data about their experiences in regular jobs. This is also one of the earlier studies to examine worker perspectives of their employers’ responses to disclosure (see also Elliott & Reuter, 2021). Compared to much prior work that was limited to disability-affirming contexts and settings, and focused on the employer perspective, the study identified considerable nuances in the contexts of disclosure and a wider range of employer responses: positive, negative, and ambiguous.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…The current study addresses important gaps in research on workplace disclosure of SMI by sampling both currently and formerly employed workers, from previously unstudied geographic contexts and a wide range of employment settings, and collecting data about their experiences in regular jobs. This is also one of the earlier studies to examine worker perspectives of their employers’ responses to disclosure (see also Elliott & Reuter, 2021). Compared to much prior work that was limited to disability-affirming contexts and settings, and focused on the employer perspective, the study identified considerable nuances in the contexts of disclosure and a wider range of employer responses: positive, negative, and ambiguous.…”
Section: Discussionmentioning
confidence: 93%
“…Prior research on disclosure has sampled current workers from single sectors or workplaces (Joyce et al, 2009; Toth & Dewa, 2014), or from mental health services agencies, where it is likely that some participants were in non-regular jobs that were obtained and/or supported by vocational services (Brohan et al, 2014; Bril-Barniv et al, 2017; Henderson et al, 2012). Prior research on employer responses has centered employer/supervisor voices (Kirsh et al, 2018; Peterson et al, 2017; Tse, 2004), or only focused on worker perspectives in the context of working professionals needing accommodations (Elliott & Reuter, 2021). We addressed these limitations by examining worker perspectives on disclosure and on their employers’ responses to disclosure among a sample of current and former workers with SMI in a wide range of professional, nonprofessional white-collar, and blue-collar regular jobs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations